2017
DOI: 10.1111/joa.12709
|View full text |Cite
|
Sign up to set email alerts
|

The biorhythm of human skeletal growth

Abstract: Evidence of a periodic biorhythm is retained in tooth enamel in the form of Retzius lines. The periodicity of Retzius lines (RP) correlates with body mass and the scheduling of life history events when compared between some mammalian species. The correlation has led to the development of the inter-specific Havers-Halberg oscillation (HHO) hypothesis, which holds great potential for studying aspects of a fossil species biology from teeth. Yet, our understanding of if, or how, the HHO relates to human skeletal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 85 publications
0
20
0
1
Order By: Relevance
“…Indeed, Mahoney et al. () have reported correlations between femur length and RP in a modern human population sample, and Hogg and colleagues (Hogg et al. ; Hogg & Bromage, ) have found correlations between human body size and RP between populations; however, regression slopes among them seem to vary (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Mahoney et al. () have reported correlations between femur length and RP in a modern human population sample, and Hogg and colleagues (Hogg et al. ; Hogg & Bromage, ) have found correlations between human body size and RP between populations; however, regression slopes among them seem to vary (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Modern humans have arguably more variation in body mass than most other mammal species, domestic dogs being one exception (Bromage et al 2016b). Indeed, Mahoney et al (2017) have reported correlations between femur length and RP in a modern human population sample, and Hogg and colleagues (Hogg et al 2014;Hogg & Bromage, 2018) have found correlations between human body size and RP between populations; however, regression slopes among them seem to vary (e.g. a positive regression slope for Indians, but a negative one for English and Peruvians), so much more work is needed in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Retzius periodicity was linked to the rate of primary bone deposition in the humeri of seven age-matched children [16]. Femoral osteocyte lacunae density was inconsistently related to RP in a sample of adult humans [15]. Thus, there is currently some evidence that suggests a relationship between RP and stature in adult humans, and between RP and primary bone growth in a small sample of infants.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The role of the infradian biorhythm for human growth and development is poorly understood. Studies of small samples of adult humans indicate that RP is negatively correlated with final attained adult stature [14,15]. This makes sense as the biorhythm is accelerated to achieve greater height within a developmental period that is constrained for humans, relative to inter-specific comparisons of RP [11].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…There is also a theory of three biorhythms that begin to act at the time of human birth [22,23]. According to various studies [22,24,25] this theory is unproven. Other data [23,26] indicate that there are interrelationships of competitive performance with the values of the three biorhythms.…”
Section: Pedagogics Psychologymentioning
confidence: 99%